Immunomodulatory Potential of Human Adipose Mesenchymal Stem Cells Derived Exosomes on in vitro Stimulated T Cells - Blazquez, Rebeca; Sanchez-Margallo, Francisco Miguel; de la Rosa, Olga; Dalemans, Wilfried; Álvarez, Verónica; Tarazona, Raquel; Casado, Javier G. (Frontiers in Immunology, 2014)
In the recent years, it has been widely demonstrated that the biological activity of mesenchymal stem cells (MSCs) is mediated through the release of paracrine factors. Many of these factors are released into exosomes, which are small membranous vesicles that participate in cell-cell communication. Exosomes from MSCs are thought to have similar functions to MSCs such as repairing and regeneration of damaged tissue, but little is known about the immunomodulatory effect of these vesicles. Based on previous reports where the immunomodulatory capacity of MSCs has been demonstrated, here we hypothesized that exosomes from MSCs may have an immunomodulatory role on the differentiation, activation and function of different lymphocyte subsets. According to this hypothesis, in vitro experiments were performed to characterize the immunomodulatory effect of MSCs-derived exosomes on in vitro stimulated T cells. The phenotypic characterization of cytotoxic and helper T cells (activation and differentiation markers) together with functional assays (proliferation and IFN-γ production) demonstrated that MSCs-derived exosomes exerted an inhibition effect in the differentiation and activation of T cells as well as a reduced T cell proliferation and IFN-γ release on in vitro expanded cells. In summary, here we demonstrate that MSCs-derived exosomes are a cell-derived product that could be considered as a therapeutic agent for the treatment of inflammation-related diseases.